Characterization and The Effects Analysis of Purple-fleshed Sweet Potato Extract (Ipomoea batatas [L.]) Administration on Triglyceride Concentration and Pancreatic Histopathology Profiles of Triton X-100-induced Hyperlipidemia in Rats - Kintoko; Hardi Astuti Witasari; Rizky Nurdhillah; Tsania Taskia Nabila (Jurnal Jamu Indonesia, 2022)
Hypertriglyceridemia occurs when the triglyceride levels are increasing from the normal (>150 mg/dL) and it causes pancreatitis at a dose of more than 885 mg/dL. The triglyceride-lowering medicines consumption has several side effects on various organ systems. The plant-based medicine (phytomedicine) alternatives have been observed as the synthetic medicine substitution. Purple-fleshed sweet potato (Ipomoea batatas [L.]) contains anthocyanin that has proven to carry out the antioxidant mechanism and the capability to be used as anti-hypertriglyceridemia. This study aims to identify the activity of purple-fleshed sweet potato extracts on triglyceride levels and the histopathological profile of rats' pancreas-induced Triton X-100. Twenty-five male Wistar rats of week 8th were divided into five groups. The normal (N) group was treated with saline solution, and the treatment (T) groups were a single dose of 100 mg/kg of body weight (BW) Triton X-100 and purple-fleshed sweet potato extracts of 175 (T1); 350 (T2); and 700 (T3) mg/kg BW, while the negative (C-) control group was mere induced by a single-dose Triton X-100 of 100 mg/kg BW. The blood serum was isolated and the pre-and post-test was subsequent conducted. The triglyceride serum levels and histopathological data were analyzed by the Kolmogorov-Smirnov normality test and Kruskal-Wallis post-test statistical analysis. The results showed that Triton X-100-induced treatment could significantly increase the triglyceride levels compared to the normal group (P<0.05). The purple-fleshed sweet potato extracts started to lower the triglyceride level at a dose of 700 mg/kg BW (51.83 ±19.15(%)). The extract doses of 175 and 350 mg/kg BW could not reduce the triglyceride level significantly (3.03±2.77 and 5.63±4.24 (%), respectively). A dose of 700 mg/kg BW did not damage the exocrine gland and Langerhans islet of hyperlipidemia rat pancreas treated by Triton X-100.